Synthesis and Antinociceptive Activity of Some Novel Nonpeptide Derivatives of interleukin-1β (193–195) Sequence - Fantetti, Lia; Adembri, Giorgio; Giotti, Alberto; Masini, Ilaria; Roncucci, Gabrio (Arzneimittelforschung, 1999)
The synthesis of a new series of nonpeptide derivatives of interleukin-l β sequence is described. Compounds have been investigated for their relative activity regarding antinociception and suppression of inflammation. Several compounds with R1(R)Lys [CH2 N]-Pro structure showed better efficacy in the inflamed paw pressure test than indometacin and morphine. In terms of the relative potencies the above mentioned products (i.e. compounds 2, 4, 5, 6; ED50 values of 0.002, 0.0035, 0.0032, 0.0074 mg/kg i.p. respectively) were 10-100 times more potent than indometacin and morphine (ED50 values of 0.22 and 0.75 mg/kg). Compounds 1–14 were not able to inhibit binding of labeled interleukin-l β to EL 4-6.1 murine cells, since they had no affinity for interleukin-l β receptors. The antinociceptive activity elicited by compound 4 in the rat inflamed paw pressure test was inhibited by naloxone, but the compound was inactive in the mouse hot plate and rat paw pressure tests. These results suggest that compound 4 exerts its antinociceptive activity through a mechanism which is based on the local release of endogenous opioids in injured tissue.
Keywords: Interleukin-1 β (193–195); antinociception; Lys-Pro-derivatives; suppression of inflammation